2021
DOI: 10.1158/2159-8290.cd-20-1661
|View full text |Cite
|
Sign up to set email alerts
|

IFNγ Is Critical for CAR T Cell–Mediated Myeloid Activation and Induction of Endogenous Immunity

Abstract: Chimeric antigen receptor (CAR) T cells mediate potent antigen-specific antitumor activity, however, their indirect effects on the endogenous immune system is not well characterized. Remarkably, we demonstrate that CAR T cell treatment of mouse syngeneic glioblastoma activates intratumoral myeloid cells and induces endogenous T cell memory responses coupled with feed-forward propagation of CAR T responses. IFNγ production by CAR T cells and IFNγ-responsiveness of host immune cells is critical for tumor immune … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 52 publications
8
83
1
Order By: Relevance
“…However, the CAR-19 infusion induced a complete tumor eradication (i.e., both CD19 wt and CD19 L174V mutated clones) and an ongoing remission of more than 2 years post-CAR-19 infusion (Figure 5a, bottom). Taken together with 6/8 patients lacking CD19 who responded to axi-cel in the ZUMA-1 registration study 6 and with recent pre-clinical studies 52,53 , these findings indicate antigen-mediated tumor killing is not the only mechanism of tumor eradication, and alternate mechanisms may predominate. Fig.…”
Section: Target-independent Car-t Anti-tumor Activitysupporting
confidence: 57%
See 1 more Smart Citation
“…However, the CAR-19 infusion induced a complete tumor eradication (i.e., both CD19 wt and CD19 L174V mutated clones) and an ongoing remission of more than 2 years post-CAR-19 infusion (Figure 5a, bottom). Taken together with 6/8 patients lacking CD19 who responded to axi-cel in the ZUMA-1 registration study 6 and with recent pre-clinical studies 52,53 , these findings indicate antigen-mediated tumor killing is not the only mechanism of tumor eradication, and alternate mechanisms may predominate. Fig.…”
Section: Target-independent Car-t Anti-tumor Activitysupporting
confidence: 57%
“…We provide cell-intrinsic alternatives to loss of the CD19 CAR target, a mechanism that, while logical, appears to be of unclear real-world importance 52,53 . In this cohort, genomic alterations of CD19 or reduced expression by flow cytometry did not significantly affect outcome, revealing for the first time that the CD19-independent genomic drivers of CAR-19 resistance appear by far the more clinically important and inter-connected with the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Their data also revealed that IL-36g armored CAR T cells activate endogenous antigenpresenting cells (APCs) and T cells through promotion of a secondary antitumor response and delayed the progression of antigen-negative tumor challenge in an experimental model of Bcell lymphoma (45). A separate study has also reported that effective CAR T cell antitumor activity of IL13Ra2-CAR T cells against mouse syngeneic glioblastoma (GBM) is significantly dependent on the activation of patient-derived endogenous T cells and monocyte/ macrophages at the tumor site in an IFNg-dependent manner (101). Currently, a phase 2 clinical trial for IL-7 and CCL-19 expressing CAR T cells against Refractory/Relapsed B Cell Lymphoma is in recruiting status (NCT03929107).…”
Section: Activation Of Endogenous Immune Systemmentioning
confidence: 99%
“…Various studies have shown that infiltration of endogenous immune cells (in particular T lymphocytes) into the tumor sites can expand the efficacy of CAR T cell therapy ( 87 , 101 ). In line with this notion, Adachi et al., reported that overexpression of IL-7 and CCL19, as two essential cytokines for generation of less-differentiated, long-lived non-exhausted (CAR) T cells and recruitment of endogenous DCs and T cells, in CAR T cells (termed 7x19 CAR T cells) increased infiltration of DCs and T cells into tumor sites following 7 × 19 CAR T cell therapy.…”
Section: Activation Of Endogenous Immune Systemmentioning
confidence: 99%
“…9 Further studies are needed to determine how the type of cell therapy used may affect the extent of antigen spreading, and how treatment strategies can potentially be combined to optimize antitumor immunity. [10][11][12][13] Open access…”
Section: Barriers To Progress Scientific Challengesmentioning
confidence: 99%